2016
DOI: 10.1007/s10545-016-9956-7
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the molecular diversity and phenotypic spectrum of glycerol 3‐phosphate dehydrogenase 1 deficiency

Abstract: Transient infantile hypertriglyceridemia (HTGT1; OMIM #614480) is a rare autosomal recessive disorder, which manifests in early infancy with transient hypertriglyceridemia, hepatomegaly, elevated liver enzymes, persistent fatty liver and hepatic fibrosis. This rare clinical entity is caused by inactivating mutations in the GPD1 gene, which encodes the cytosolic isoform of glycerol-3-phosphate dehydrogenase. Here we report on four patients from three unrelated families of diverse ethnic origins, who presented w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 18 publications
2
27
1
Order By: Relevance
“…In addition, other forms of nephrotoxicity such as cisplatin-or glycerolinduced CKD are associated with abnormal Ggt1 and Gyk expression (74,75); in this study, we found that they also contributed to lipotoxicity. Hmgcs1, Phyh, and Gpd1 were, for the first time to our knowledge, found to be associated with nephrotoxicity, a finding that was also supported by previous reports that they were involved in cholesterol synthesis and steatosis (76)(77)(78). Moreover, these pathways or factors were reversed by troxerutin, suggesting a protective effect of troxerutin in reducing renal lipotoxicity.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, other forms of nephrotoxicity such as cisplatin-or glycerolinduced CKD are associated with abnormal Ggt1 and Gyk expression (74,75); in this study, we found that they also contributed to lipotoxicity. Hmgcs1, Phyh, and Gpd1 were, for the first time to our knowledge, found to be associated with nephrotoxicity, a finding that was also supported by previous reports that they were involved in cholesterol synthesis and steatosis (76)(77)(78). Moreover, these pathways or factors were reversed by troxerutin, suggesting a protective effect of troxerutin in reducing renal lipotoxicity.…”
Section: Discussionsupporting
confidence: 89%
“…And the persistent high level of DHEA‐S in the patient may due to his hepatic steatosis resulting in the increased 5β‐reductase activities (Westerbacka et al, ). GPD1 deficiency can lead to non‐alcoholic hepatic steatosis (NASH) (Dionisi‐Vici et al, ), which could be a risk factor for the development of an overt metabolic syndrome, such as type 2 diabetes and insulin resistance (Marchesini et al, ). Our patient was diagnosed with fatty liver and obesity, whereas the affected individuals described in previous reports had fatty liver with normal BMI.…”
Section: Discussionmentioning
confidence: 99%
“…More intriguingly, both of the patient's parents had an unsatisfactory height and his mother was overweight. Moreover, Dionisi‐Vici et al () reported a patient (patient B) that both of her parents had fatty liver. It seems that the GPD1 mutation carrier could have some lighter clinical features, which requires more clinical information from future report cases to confirm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported biallelic mutations in GPD1 gene of a Chinese boy who presented with a different phenotype comprising obesity, insulin resistance, fatty liver, and short stature [ 4 ]. To date, only four reports have described 16 patients harboring homozygous or compound heterozygous mutations in the GPD1 gene [ 3 6 ]. Here, we describe a Han Chinese patient with a novel GPD1 homozygous mutation who presented with hepatomegaly, elevated transaminases, hypertriglyceridemia, and fatty liver in infancy.…”
Section: Introductionmentioning
confidence: 99%